Transformation of Public Relations Strategies in the Digital Age: Analysis of Public Communication Adaptation in Educational Institutions - Gunawan, Reski; Widianti, Windi; Romlah, Romlah; Wakhid, Ali Abdul (Ahlussunnah: Journal of Islamic Education, 2025)
Digital transformation has brought fundamental changes to public relations practices in Indonesia. The role of public relations is no longer merely as a conveyor of information, but has evolved into a reputation manager and guardian of public trust in the dynamic era of digital communication. This study aims to analyze the transformation of public relations strategies in facing the challenges and opportunities of digital communication, as well as how these innovations contribute to the formation of a credible and adaptive institutional image. This study uses a literature review method, examining various research results and scientific publications from 2019 to 2024 that are relevant to the themes of digital public relations strategies, public communication, and reputation management. The results of the study show that the transformation of public relations strategies includes changes in the aspects of role, technology, and ethical orientation. Public relations practitioners are required to master digital literacy, public data analysis, and the ability to manage issues and crises in the online space. In addition, the use of artificial intelligence (AI), chatbots, and social listened strengthens the effectiveness of communication, although it needs to be balanced with the principles of transparency and social responsibility. The conclusion of this study confirms that the success of public relations in the digital era depends on the ability to integrate technology, creativity, and human values to build a sustainable institutional reputation.